Evaluation of diet formulation based on digestible amino acids and true metabolizable energy on broiler breeder performance - Nasr, J. (Cuban Journal of Agricultural Science, 2016)
A study was conducted to determine the effects of the formulation of diets based on digestible amino acids of feeds and nitrogen corrected apparent metabolizable energy on the performance of Arian broiler breeder from 50 to 64 weeks old. Four treatments with six replicates (7 females with a male) were applied, using a completely randomized experimental design and a 2 × 2 factorial arrangement. Four experimental diets were formulated based on two factors: first, two levels of Apparent and True Metabolizable Energy corrected for Nitrogen (AMEn and TMEn) and second, two levels of Total (TAA) and Digestible Amino Acids (DAA) of feeds. Feeding broiler breeders AMEn diet significantly increased egg weight, while the egg mass, fertility and hatchability were significantly different, which were affected by diets formulation based on energy (P<0.05). Diet formulated with DAA significantly improved egg weight, Haugh unit and fertility (P<0.01). Treatment 2 (AMEn+TAA) was significantly highest in egg weight, (68.97 g); egg mass, (43.1 g/hen/day); albumen height, (7.96 mm); Haugh unit, (86.32); fertility, (81.51 %); hatchability, (64.69 %); chicken weight, 50.27 (g) and amount of chickens per hen, (34.3) (P<0.05). This experiment showed that diet formulation based on AMEn + DAA for broiler breeder significantly increased performance. Key words: broiler breeders, energy, amino acids, chicken.